How common and what are the determinants of sub-optimal care for Parkinson's disease patients: the Milton Keynes community study. - Hu, M; Butterworth, R; Kumar, V; Cooper, J; Jones, E; Catterall, L; Ben-Shlomo, Y (2011)
OBJECTIVES: Limited data currently exists within the UK addressing the level of Parkinson's disease (PD) healthcare provision. We investigated whether care for PD patients in a UK community met national guidelines, and the determinants of sub-optimal care for this patient group. METHODS: 340 PD patients were identified from a population of 242,606 (crude prevalence 140 per 100,000 (95% CI 126-156 per 100,000), age-adjusted prevalence 199 per 100,000 (95% CI 178-221 per 100,000)). 248 out of 340 (73%) PD patients identified took part, completing rating scales assessing cognitive, non-motor and sociodemographic variables. RESULTS AND CONCLUSIONS: 9% of patients had never seen a neurologist for their PD and 18.5% were sub-optimally managed; defined as (a) delay between initial diagnosis and first consultation by a specialist >1 year and (b) patients who had not had specialist PD review for >1 year. Older age, poor cognition and worse mobility were major factors in determining sub-optimal care whilst lower education level and tremor as initial symptom were more modest predictors. 20% of patients had been started on dopaminergic therapies including ergot-derived agonists by their GP prior to referral and less than a third had seen allied health professionals throughout their illness. Further work is required to test whether these findings are generalizable across the country and identify what can be done to ensure equal access to specialist care so that all PD patients have access to best practice.